Sistem Informasi Pengelolaan Dana Desa Kabupaten Klaten - Puspitasari, Norma; Wahyudi, Muhammad Hari; Damayanti, Wandha (Politeknik Indonusa Surakarta, 2020)
Currently, the Klaten Regency Discominfo requires a village fund management system for transparency to the community. In the current system, data management in terms of village fund transparency is still manual and not computerized properly, so that the process of transparency in managing village funds to the community is still in the form of a large baleho which is often damaged due to several factors, namely vandalism and natural factors.The purpose of this system is to facilitate the management of village funds, to facilitate the transparency of village funds to the community. The method used is the waterfall method starting from working on a system that is carried out sequentially or linearly with needs analysis, system design, program coding, program testing, program implementation.The final result obtained by the creation of an information system for managing village funds in the Klaten district by applying the Laravel framework, the Klaten district village government can report the transparency of village fund management to the community. With the results of the system that can be accessed by admins and users, namely news data, income data, expenditure data, and print reports.